Temporomandibular joint kinematic changes in pregnant women: a case-control study - Elbesh, Rovan M.; Helmy, Amany Mahmoud; Hamada, Hamada Ahmed; Ali, Salah S.; Ashour, Reda Sayed (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Misalignment of the mandible and pelvis during pregnancy may result in pelvic and temporomandibular disorders, necessitating an understanding of timing and features for effective prevention and management of these conditions. The study measured and compared lumbopelvic parameters, temporomandibular joint variables, and temporomandibular disorders between primigravida and nulligravida women at four-time points.Methods. The study involved 100 Egyptian women from El-Hosiery Women’s Health Care Center, with no significant differences in age or height (p > 0.05) (mean age = 23.05 ± 0.67 years; height = 162.52 ± 3.36 cm). Data analysis used a mixed-design multivariate analysis of variance (MANOVA) with a 2 × 4 factorial arrangement to compare the relevant variables between both groups. The researchers employed a pelvic inclinometer, a digital inclinometer, and the Fonseca Anamnestic Index to measure lumbopelvic variables, temporomandibular joint kinematics, and temporomandibular disorders, respectively. Assessments commenced at the start of the last week of each trimester, three months postpartum for primigravida, and at the end of the menstrual cycle of the corresponding month for nulligravida participants.Results. Significant differences (p < 0.05) were observed between groups for the biomechanical variables and clinical signs of temporomandibular disorders.Conclusions. Throughout the trimesters and postpartum period, the study revealed significant differences in lumbopelvic parameters, temporomandibular joint variables, and temporomandibular disorders between primigravida and nulligravida participants.
Keywords: pregnancy; kinematics; temporomandibular joint disorders; nulligravida; primigravity